Schematic language in movies: an analytical approach - Aragão, Isabella R.; Coutinho, Solange G. (InfoDesign, 2008)
The purpose of this paper is to highlight the use of schematic language in recently produced dominantly narrative feature films. More specifically, the aim is to observe its elements by using the classification proposed by Aragão (2006), in which ten syntactic and semantic categories are defined, taking into account design and cinema theories. Three graphic cinematographic configurations of three different movies were chosen: the trajectory of a suicide in Magnolia (Paul Thomas Anderson, 1999), the musical score of the last concert in Tônica Dominante (Lina Chamie, 2000), and the scenario of Dogville (Lars Von Trier, 2003). In all scenes, the schematic elements carry informational contents, that is, they are dominant factors for the meaning of the graphic configuration. After the analysis, there follows some considerations regarding these elements in the movies, aiming to establish links between the categories and also raise certain questions for debate.